2020
DOI: 10.1097/meg.0000000000002025
|View full text |Cite
|
Sign up to set email alerts
|

Continuous insulin therapy versus apheresis in patients with hypertriglyceridemia-associated pancreatitis

Abstract: Background The optimal treatment modality for lowering the triglyceride level in patients with hypertriglyceridemia (HTG)-associated acute pancreatitis is unknown. We evaluated the efficacy of continuous insulin infusion and apheresis procedures as triglyceride-lowering therapy. Materials and methods Clinical, demographic, and laboratory data were retrospectively evaluated for patients with HTGassociated pancreatitis who received continuous insulin infusion or apheresis in a single tertiary center. The endpoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 37 publications
(54 reference statements)
1
24
0
Order By: Relevance
“…There were rare attempts in the literature at a controlled comparison of PE with conservative treatments, showing greater triglyceride lowering with PE in some ( 8 , 13 , 17 , 22 ) but not all reports ( 23 , 24 ). E.g., we have shown a 59% vs. 27% daily reduction in triglycerides with PE as compared to fasting-only 24-hour periods in between PE treatments ( 8 ), with the limitation, that the fasting periods usually did not occur on the day of admission and that the% reduction in triglycerides is likely higher with higher baseline triglyceride level.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There were rare attempts in the literature at a controlled comparison of PE with conservative treatments, showing greater triglyceride lowering with PE in some ( 8 , 13 , 17 , 22 ) but not all reports ( 23 , 24 ). E.g., we have shown a 59% vs. 27% daily reduction in triglycerides with PE as compared to fasting-only 24-hour periods in between PE treatments ( 8 ), with the limitation, that the fasting periods usually did not occur on the day of admission and that the% reduction in triglycerides is likely higher with higher baseline triglyceride level.…”
Section: Discussionmentioning
confidence: 99%
“…E.g., we have shown a 59% vs. 27% daily reduction in triglycerides with PE as compared to fasting-only 24-hour periods in between PE treatments ( 8 ), with the limitation, that the fasting periods usually did not occur on the day of admission and that the% reduction in triglycerides is likely higher with higher baseline triglyceride level. Another retrospective study found a significantly higher baseline triglycerides in the apheresis group and comparable levels after 24 h, resulting in a 79% decrease with apheresis versus 44% with insulin infusion ( 17 ). In a relatively large propensity score-matched cohort of patients, a modest but significantly greater reduction in triglycerides was seen with DFPF (80%) versus conservative treatment (72%), which included insulin only in cases of hyperglycemia ( 13 ); a result comparable to this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations